Houses in Memory of Nadežda Petrović, Part II: Traces of Memory and Archival Sources — The Petrović House at Ratarska 32 (Knjiženstvo, journal for studies in literature, gender and culture, 2025)
This work examines the complex relationship between individual memory, collective memory, and the documentary materials that emerge from them. By analyzing two seemingly divergent approaches to interpreting personal remembrance and cultural collective memory, the study grounds itself in Jan Assmann’s theory of cultural memory. According to Assmann, the individual is always the subject of memory and remembrance, yet personal memory is shaped by the social frameworks that organize the individual. This perspective aligns with contemporary cultural theories that recognize the role of family heritage in shaping cultural identity. Within this conceptual framework—which places family memory on equal footing with collective memory—the paper explores the historical continuity of the Petrović family, with particular attention to Ljubica Luković, one of the daughters of Dimitrije and Mileva Petrović.The family’s presence at Ratarska 32 is reconstructed through the long-term recollections shared in direct conversations between the author and Mr. Miloš Kolaž. A second, documentary mode of remembering is developed through the analysis of archival records that identify the house at Ratarska 32 as a site of memory. These documents provide deeper insight into the social era in which the Petrović family lived, formed individual identities, shaped their family identity, and contributed significantly to the development of cultural collective memory.The aim of this work is to understand how individual memory, collective cultural memory, and documentary memory intersect to form a foundation for researching cultural heritage. The study is supplemented with archival materials related to the Petrović family home at the former Ratarska 32, the scholarly work of historian Dimitrije Mita Petrović, and family correspondence. These materials support the argument that documentary analysis contributes to establishing an objective framework for understanding personalities and events that are otherwise viewed from a considerable temporal distance.
Keywords: memory; Petrović family; Ljubica Luković; Rastko Petrović; documentary material; cultural heritage